PENGEMBANGAN BAHAN AJAR INOVATIF RUMUS KIMIA DAN PERSAMAAN REAKSI BERBASIS MODEL PEMBELAJARAN PROBLEM BASE LEARNING (PBL) - Ramlan Silaban; Saronom Silaban; Freddy T.M. Panggabean; Elsa Ginting (Pascasarjana Universitas Negeri Medan, 2015)
Abstract The research aims to get an innovative chemistry teaching module on chemical formula and chemical equilibrium for X grade SMA to improve student learning outcomes. This research conduct in some senior high school (SMA) in North Sumatera whose devide in two class, those experiment and control class. This R&D type modifies from Borg&Gall theory, and some textbook contain this subject has been analyzing using BSNP criteria. The composed innovative teaching module trial on classroom by quasy-experiment methods. The experiment class taught using innovative teaching module and control class using textbook. The results showed that (1) Some chemistry textbook contain this subject which produced by some publisher has good quality but there are some sequences material and teaching strategy will be addition to completely them. (2) We have get a composing innovative teaching module on chemical formula and chemical equilibrium for X grade SMA on chemical formula and chemical equilibrium with combine PBL teaching model. This module have been standardization and fully criteria of BSNP. (3) There is a significant increasing of chemistry student learning outcomes using this innovative module on teaching classroom Keywords : development innovative teaching module; PBL model; learning outcomes